The Influence of Organizational Climate and Transformational Leadership Style on Teacher Performance at SMK 3 Sukawati with Self-Efficacy as a Mediating Variable - I Gede Agus Sentana Widana Yasa; I Nengah Suardika; Made Ika Prasetyadewi (International Journal of Economics and Management Sciences, 2025)
Education plays a vital role in improving human resource quality, making it essential for addressing challenges in developing countries, such as inequality, poverty, and cultural instability. Teachers, as key facilitators in the learning process, are central to achieving educational goals, with performance influenced by internal factors like self-efficacy and external factors like organizational climate and leadership style. This study examines the influence of organizational climate and transformational leadership on teacher performance at SMK 3 Sukawati, with self-efficacy as a mediating variable. The population and sample include all 55 teachers, selected through purposive sampling. Data were collected via questionnaires, interviews, and documentation, then analyzed using path analysis. Results show that organizational climate and transformational leadership positively and significantly affect both teacher performance and self-efficacy. Self-efficacy also positively and significantly influences performance. Additionally, organizational climate and transformational leadership indirectly impact teacher performance through self-efficacy.